WRITTEN RETELLING VS ORAL RETELLING: AN EVALUATION STRATEGY IN AN ESL CLASSROOM - Domingo, Dahlia R. (PEOPLE: International Journal of Social Sciences, 2015)
Written and oral retellings of stories appear to have potential for skill development inside English as a Second Language (ESL) classroom. However, while they appear to have potential for skill development they have not been widely tested (Morrow, 1986), There are some evidences written and oral retellings as an instructional strategy enhance the development of various literacy skills (Golden 1984, and Whaley, 1981). Although there is support for the use of retellings as a strategy to enhance learner’s literacy development, Morrow (1985) stated that the use of oral and written retellings was not widely practiced in schools since teachers viewed retellings as time consuming and difficult (Morrow, 1985).This mini research compares written and oral retellings and would like to prove that the skill of retelling aside from contributing to student’s skill development is an effective instrument in measuring comprehension, thus enhances both oral and written skills of students. This research illustrates though oral and written retellings are different, it also shows how similar they are.